The adoption and diffusion of organizational innovation: evidence for the US economy - Lisa M. Lynch (Institute for the Study of Labor (IZA), 2007)
Using a unique longitudinal representative survey of both manufacturing and non-manufacturing businesses in the United States during the 1990's, I examine the incidence and intensity of organizational innovation and the factors associated with investments in organizational innovation. Past profits tend to be positively associated with organizational innovation. Employers with a more external focus and broader networks to learn about best practices (as proxied by exports, benchmarking, and being part of a multi-establishment firm) are more likely to invest in organizational innovation. Investments in human capital, information technology, R&D, and physical capital appear to be complementary with investments in organizational innovation. In addition, non-unionized manufacturing plants are more likely to have invested more broadly and intensely in organizational innovation.
urn:nbn:de:101:1-20080401119
Keywords: 330; Unternehmensorganisation; Organisationsverhalten; Innovation; Bildungsinvestition; Informationstechnik; Betriebliche Forschung; Gewerkschaftlicher Organisationsgrad; USA